The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1516-14392013005000095
|View full text |Cite
|
Sign up to set email alerts
|

Case depth in SAE 1020 steel using barkhausen noise

Abstract: The most widely used thermochemical process for surface hardening of steels is case hardening. Using several different heat treatments, martensitic surface layers were formed on SAE 1020 steel into which carbon had been diffused. Case depths were measured by traditional destructive techniques. Barkhausen noise measurements were made and both the RMS Barkhausen pulse envelope and the fast Fourier transform (FFT) were obtained from numerical calculation. The FFT amplitudes, functions of frequency, were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Those changes in the magnetic flux can be observed by a coil located at the surface of the material, in the form of voltage noise induced in its turn as a result of rapid changes in the degree of magnetization [ 4 ]. This method is used for various industrial applications for non-destructive condition testing and quality assessment of ferromagnetic materials, e.g., for evaluation of residual stress, active tensile and compressive stress, microstructure and micro hardening [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In addition to the possible applications mentioned above, the MBN is also used to evaluate the directional properties of ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Those changes in the magnetic flux can be observed by a coil located at the surface of the material, in the form of voltage noise induced in its turn as a result of rapid changes in the degree of magnetization [ 4 ]. This method is used for various industrial applications for non-destructive condition testing and quality assessment of ferromagnetic materials, e.g., for evaluation of residual stress, active tensile and compressive stress, microstructure and micro hardening [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In addition to the possible applications mentioned above, the MBN is also used to evaluate the directional properties of ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these obstacles arising in the material require additional energy and cause discontinuous changes of the magnetic state. This phenomenon has been studied and gradually used for non-destructive testing (NDT) of materials [4,5,6,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. The stepwise change of the magnetization level during operation of the alternating magnetizing field can be observed by coil placed in the neighbourhood of the material.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a voltage U BN called the Barkhausen Noise (BN) is induced in coil. The Magnetic Barkhausen Noise method (MBN) is used mainly for [29]: detection and evaluation of fatigue and stress [4,5,6,11,12,16,17,22,24,26,31,32,34,35,36,37,38,39], material microstructure [19,20,28,37,38,40] and microhardness (i.e., hardening level, case depth) analysis [13,14,23,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the ratio of two voltage sweeps with different frequencies produces a good estimation of the case depth. Drehmer et al [34] applied BHN measurement for estimating the case depth of SAE 1020 steel. They used RMS Barkhausen pulse envelope and fast Fourier transforms (FFT) to estimate case depths.…”
Section: Introductionmentioning
confidence: 99%